2022
DOI: 10.1155/2022/6009787
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Regulators of Aging and Age-Related Macular Degeneration in the Retinal Pigment Epithelium

Abstract: Age-related macular degeneration (AMD), the leading cause of blindness in elderly populations, involves the loss of central vision due to progressive dysfunction of the retinal pigment epithelium (RPE) and subsequent loss of light-sensing photoreceptors. While age is a key risk factor, not every aged individual develops AMD. Thus, the critical question is what specific cellular changes tip the balance from healthy aging to disease. To distinguish between changes associated with aging and AMD, we compared the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 62 publications
0
9
0
1
Order By: Relevance
“…Three mitochondrial ribosomal proteins (MRPS30, MPRS15, MPRS9) and five proteins involved in mitochondria trafficking and assembly (TSPO, PARL, TMEM126A, RHOT2, TOMM40L) were increased, indicating a potential compensatory response to mitochondrial damage caused by disease conditions. The upregulation of four enzymes of glycolysis (HK1, HK2, PKM, OGDHL) in MGS2 samples is consistent with the increased glycolytic proteins in RPE with AMD [ 22 ]. Interestingly, some enzymes involved in oxidative phosphorylation were also increased at the early stage.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Three mitochondrial ribosomal proteins (MRPS30, MPRS15, MPRS9) and five proteins involved in mitochondria trafficking and assembly (TSPO, PARL, TMEM126A, RHOT2, TOMM40L) were increased, indicating a potential compensatory response to mitochondrial damage caused by disease conditions. The upregulation of four enzymes of glycolysis (HK1, HK2, PKM, OGDHL) in MGS2 samples is consistent with the increased glycolytic proteins in RPE with AMD [ 22 ]. Interestingly, some enzymes involved in oxidative phosphorylation were also increased at the early stage.…”
Section: Discussionmentioning
confidence: 63%
“…In our previous studies, we investigated RPE proteomic changes at different stages of AMD using 2-DE coupled to either MALDI-TOF or LC-MS/MS [ 9 , 21 , 22 ]. In the first study, we identified eight spots with significant changes in AMD samples, including three ATP synthase subunits, cytochrome c oxidase VIb, mitofilin, mtHsp70 and mitochondrial translation factor Tu, which are proteins that reside in the mitochondria [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress underlies the pathophysiology of AMD [ 139 ]. Harmful reactive oxygen intermediates are produced at the retina from oxygen consumption, irradiation, oxidation of the fatty acids of the photoreceptor outer segment membrane, photosensitizers at the neurosensory retina and the RPE, and RPE phagocytosis [ 140 , 141 , 142 ].…”
Section: Age-related Eye Disease and The Role Of Oxidative Stressmentioning
confidence: 99%
“…It has been shown that the AMD retina is under increased oxidative stress in comparison with the age-matched retina and there is a growing body of evidence suggesting that the oxidative stress and products of lipid and bisretinoid oxidation can contribute to the development and progression of AMD by activation of the complement cascade, and other proinflammatory and proangiogenic signalling (reviewed in [193,[380][381][382][383][384][385]). Firstly, RPE affected by early, atrophic, and exudative AMD exhibit about five-fold increased content of total iron and iron chelateable by desferrioxamine in comparison with RPE in age-matched normal retinas [386]. It has been shown in experiments on mice that the retinal iron overload, caused by intravitreal injection of ferric ammonium citrate into the eye, results in i) the modification of proteins by a characteristic product of DHA oxidation forming CEP; ii) the upregulation of interleukin-1β (IL-1β) and cluster of differentiation 68 (CD68) expression; and iii) the photoreceptor and RPE atrophy [93,387].…”
Section: Current Evidence For Increased Oxidative Stress and Oxidativ...mentioning
confidence: 99%